Pleomorphic adenoma of the upper lip: A case report - Shrestha, A; Reddy, NS; Ganguly, SN (Journal of College of Medical Sciences-Nepal, 2010)
This case report describes a rare and unusual lesion found in 27 year old female, which was diagnosed as pleomorphic adenoma of the minor salivary glands in the upper lip. The tumor was a circumscribed, large firm mass, about 5 cm in diameter, almost obstructing the nasal vestibule and characterized by slow growth. Complete excision was performed and the histopathological analysis showed pleomorphic adenoma. The tumor did not recur. A brief review of the relevant literature is also presented. Keywords: Pleomorphic adenoma; minor salivary gland tumors; nasal vestibule DOI: 10.3126/jcmsn.v6i1.3603 Journal of College of Medical Sciences-Nepal, 2010, Vol. 6, No. 1, 51-53